Genetic variation and phylogenetic relationships of Nigerian indigenous and commercial pigs in southwestern Nigeria - Oluwole, O.O.; Okoth, Edward A.; Adeola, A.C.; Ogugo, Moses (2022)
This work presents an initial observation in a continuing study of genetic diversity and relationships of Nigerian Indigenous Pig (NIP) in southwestern Nigeria with commercial pigs using microsatellite markers. Sixty individuals including Nigerian indigenous pigs (NIP) (n=25), exotic (n=25), and crosses between the exotic pigs (n=10) were genotyped based on eight microsatellite markers. The mean number of alleles observed in the overall population of the three populations was 3.63±0.36. Allele frequency ranged from 0.00 to 1.00 from the 39 alleles obtained within the population. These allele frequencies obtained from the interpretation for the microsatellite loci across the three populations were polymorphic except for S0101 which was monomorphic. The mean number of the effective allele was 2.22±0.17. The means obtained in this study for observed and expected heterozygosities were 0.53 and 0.50 respectively. The F-statistics showed a reduction in heterozygosity at various loci across the population. The low mean level of gene flow among the population was estimated to be 9.18±3.59. The very low genetic differentiation between NIP and commercial pigs reflects high gene flow. The phylogenetic tree separated the NIP from the two populations while the exotic and the crosses clustered closely. These results show that there is low genetic variation among the populations studied.